The first stage of Australia's digital transition and its implications for Australian television drama. (February 2022) - Potter, Anna; Lotz, Amanda D.
This article analyses how digitisation and screen policy reform altered the production of domestic drama and children's programmes in Australia. Focusing on dynamics that developed before widespread use of streaming services, it maps the disruptions and evolution that digital 'multi-channels' caused and how they challenged audiovisual policy frameworks intended to safeguard local television including drama on advertiser-funded broadcasters. The article reveals how the effects of fragmentation undermined commercial television's business model and eroded investment in scripted content. Shifting policy priorities also brought new support mechanisms for local programmes and led to adjustments to the ABC's drama funding practices, with significant effects on the form, content, and cultural visibility of Australian drama. This initial stage of digital disruption – spanning roughly 2001–2014 – is often overlooked but is crucial for appreciating the challenges facing Australian television drama production in the 2020s.